1992
DOI: 10.1177/016264349201100404
|View full text |Cite
|
Sign up to set email alerts
|

Voice Recognition Technology and Persons with Severe Mental Retardation and Severe Physical Impairment: Learning, Response Differentiation, and Affect

Abstract: This study investigated the learning and response differentiation of a variety of voice commands that served to control environmental devices by a person who is severely mentally retarded and severely physically impaired. The contingencies between vocalization and device activation were created by a computer system with voice recognition and environmental control capabilities. Using a multiple-baseline-across-behaviors experimental design, the study shows that the subject (a) learned the cause-and-effect relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Early studies of discrete utterance SR technology demonstrated higher levels of recognition accuracy than this project, but for smaller vocabulary sets. [8][9][10][11][12] A paired down version of the SSR may be needed so that the recognition accuracy is in alignment with the improvements that were noted in acoustic performance in this study.…”
Section: Future Directionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Early studies of discrete utterance SR technology demonstrated higher levels of recognition accuracy than this project, but for smaller vocabulary sets. [8][9][10][11][12] A paired down version of the SSR may be needed so that the recognition accuracy is in alignment with the improvements that were noted in acoustic performance in this study.…”
Section: Future Directionsmentioning
confidence: 85%
“…Early studies using discrete utterance, speaker-dependent systems yielded mixed results because of differing severity levels and differences in amount of speech production variability speakers exhibited. [8][9][10][11][12] These studies examined recognition accuracy with limited vocabulary sets (e.g., alphanumeric codes, sentences, or short, standardized reading passages).…”
mentioning
confidence: 99%
“…A wide range of AT devices exist that can support students' educationallyrelated functions, specifically for physical access, cognitive and learning access, communication access, and sensory access (Brown & Cavalier, 1992;Crandall, Gerrey, & Braybyn, 1994;Englert, Manalo, & Zhao, 2004;Lee & Vail, 2005;MacArthur & Cavalier, 2004;Ripat & Strock, 2004;Williams, 2002). Some examples of AT devices commonly used by students with disabilities to participate in school settings include power wheel chairs, voice input and output software and hardware, reading and writing enhancement software, augmentative communication devices that "speak" for the non-speaking student, and visual enlargement or assistive listening devices for students with visual or hearing impairments (Brown & Cavalier, 1992;Crandall, Gerrey, & Braybyn, 1994;Englert, Manalo, & Zhao, 2004;Lee & Vail, 2005;Macarthur & Cavalier, 2004;Ripat & Strock, 2004;Williams, 2002).…”
Section: At and Factors Influencing Student Support In Educational Sementioning
confidence: 99%
“…Successful student use of AT depends upon the presence of many factors involved with AT implementation (Hutinger, Johanson, & Stoneburner, 1996;Riemer-Reiss & Wacker, 2000;Todis, 1996). Access alone is not sufficient to ensure success in AT use (Boone & Higgins, 2007;Brown & Cavalier, 1992;Mirenda, Turoldo, & McAvoy, 2006;Stoner, Esterbrooks, & Laughton, 2005;Tumlin & Heller, 2004).…”
Section: Summation Of Literature Review Findingsmentioning
confidence: 99%
“…A wide range of AT devices exist that can support students' educationallyrelated functions, specifically for physical access, cognitive and learning access, communication access, and sensory access (Brown & Cavalier, 1992;Crandall, Gerrey, & Braybyn, 1994;Englert, Manalo, & Zhao, 2004;Lange, McPhillips, Mulhern, & Wylie, 2006;Lee & Vail, 2005;MacArthur & Cavalier, 2004;Ripat & Strock, 2004;Williams, 2002). Some examples of AT devices commonly used by students with disabilities to participate in school settings include power wheel chairs, voice input and output software and hardware, reading and writing enhancement software, augmentative communication devices that "speak" for the non-speaking student, and visual enlargement or assistive listening devices for students with visual or hearing impairments (Brown & Cavalier, 1992;Crandall, Gerrey, & Braybyn, 1994;Englert, Manalo, & Zhao, 2004;Lange, McPhillips, Mulhern, & Wylie, 2006;Lee & Vail, 2005;Macarthur & Cavalier, 2004;Ripat & Strock, 2004;Williams, 2002).…”
Section: At and Factors Influencing Student Support In Educational Sementioning
confidence: 99%